2021
DOI: 10.3389/fimmu.2021.665183
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Sympathetic Hyperactivity in Severe Anti-N-Methyl-d-Aspartate Receptor Encephalitis: A Single Center Retrospective Observational Study

Abstract: BackgroundParoxysmal sympathetic hyperactivity (PSH) is a disorder with excessive sympathetic activity commonly recognized in patients with acquired brain injury. Autonomic instability is frequent in anti-N-methyl-d-aspartate receptor encephalitis (anti-NMDARE). However, PSH in anti-NMDARE has gained little attention.MethodsWe retrospectively reviewed 24 patients diagnosed with severe anti-NMDARE in the neuro-intensive care unit (NICU) between 2014 and 2019. Patients were assessed with the PSH assessment measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Paroxysmal sympathetic hyperactivity (PSH) is commonly seen in acquired brain injury and is characterized by episodic tachycardia, hypertension, tachypnea, hyperpyrexia, diaphoresis, and abnormal motor posturing. A recent retrospective study of 24 patients with NMDA encephalitis found PSH in 50% of cases [ 7 ]. The prevalence was lower at 9% in a larger study involving 132 patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal sympathetic hyperactivity (PSH) is commonly seen in acquired brain injury and is characterized by episodic tachycardia, hypertension, tachypnea, hyperpyrexia, diaphoresis, and abnormal motor posturing. A recent retrospective study of 24 patients with NMDA encephalitis found PSH in 50% of cases [ 7 ]. The prevalence was lower at 9% in a larger study involving 132 patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSH was also associated with worse outcomes such as prolonged hospitalization, neuro-ICU stays, and mechanical ventilation. Symptoms were mainly controlled with propranolol and clonazepam [49]. When managing autonomic dysfunction in patients with AE, it is essential to rule out other possible causes that may have similar presentations with dysautonomia, such as metabolic dysfunction, drug toxicities, and infections [47].…”
Section: Dysautonomiamentioning
confidence: 99%
“…Риск развития ПСГА выше у больных с тяжелыми ЧМТ (до 80% всех случаев ПСГА) [14,15], внутричерепными кровоизлияниям, гипоксическими, дисметаболическими (в частности, гипогликемическими) повреждениями головного мозга, внутричерепной гипертензией (ВЧГ), в том числе вследствие гидроцефалии. Реже синдром ПСГА развивается у пациентов с опухолью ГМ, острыми нарушениями кровообращения (ОНМК) по ишемическому типу, менингитом, энцефалитом [16][17][18]. Обзор 349 опубликованных наблюдений ПСГА показал, что в 80% случаев синдром развивался после ЧМТ, 10%у больных с постаноксической энцефалопатией, 5% -после ОНМК, а остальные 5% были связаны с гидроцефалией, опухолью, гипоглиw w w .…”
Section: Introductionunclassified